1971
DOI: 10.1021/jf60174a009
|View full text |Cite
|
Sign up to set email alerts
|

Thiopropanal S-oxide: a lachrymatory factor in onions

Abstract: The lachrymatory factor in onions was isolated by gas chromatography of a raw onion extract. By means of spectral analysis, the isolate was identified as thiopropanal S-oxide. Synthesis confirmed this identification. Thioethanal, thioacetone, thiobutanal, and thiohexanal S-oxides were also synthesized and their lachrymogenic properties were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 7 publications
2
54
0
Order By: Relevance
“…Cyclodextrin use will be limited to very special applications where competing processes fail or where very high value materials must be protected. Coacervation has found limited use in flavor encapsulation (56)(57)(58). However, work is currently in progress on this method and perhaps we will see its application in the future (59)(60)(61); it is therefore considered in this review.…”
Section: Ch 2 Ohmentioning
confidence: 99%
“…Cyclodextrin use will be limited to very special applications where competing processes fail or where very high value materials must be protected. Coacervation has found limited use in flavor encapsulation (56)(57)(58). However, work is currently in progress on this method and perhaps we will see its application in the future (59)(60)(61); it is therefore considered in this review.…”
Section: Ch 2 Ohmentioning
confidence: 99%
“…In Cavallito's studies, antimicrobial activity was found neither with aqueous garlic extracts lacking allicin nor following the addition of GO or diallyl sulfides (5) and no allyl sulfides were found in freshly prepared aqueous garlic clove extracts (6). Also, an early gas chromatographic study (4) indicated that the relatively rapid decomposition of allicin present in aqueous garlic extracts (14) involved transformation mainly to diallyl sulfides. For these reasons it was concluded that GO and its constituent sulfides lack antimicrobial activity.…”
mentioning
confidence: 99%
“…The substance causing this irritation, a lachrymatory factor (LF), was identified as propanethial S-oxide by Brodnitz and Pascale more than 35 years ago. 1) LF belongs to the group of thioaldehyde S-oxides, and to date, only three other naturally occurring thioaldehyde S-oxides have been reported: (Z,Z)-d,l-2,3-dimethyl-1,4-butanedithial S,S 0 -dioxide from onion;…”
mentioning
confidence: 99%